2017
DOI: 10.1103/physreva.96.032114
|View full text |Cite
|
Sign up to set email alerts
|

Weak value beyond conditional expectation value of the pointer readings

Abstract: It is argued that a weak value of an observable is a robust property of a single pre-and postselected quantum system rather than a statistical property. During an infinitesimal time a system with a given weak value affects other systems as if it were in an eigenstate with eigenvalue equal to the weak value. This differs significantly from the action of a system pre-selected only and possessing a numerically equal expectation value. The weak value has a physical meaning beyond a conditional average of a pointer… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
85
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(86 citation statements)
references
References 66 publications
1
85
0
Order By: Relevance
“…by computing the predictability. We also note that Alice and Bob may switch roles and achieve similar results; this fact is manifested in (27) by noting the expression is invariant under permutation of the two particles.…”
Section: Model For Asymmetric Entangled Double-slit Experimentsmentioning
confidence: 74%
See 2 more Smart Citations
“…by computing the predictability. We also note that Alice and Bob may switch roles and achieve similar results; this fact is manifested in (27) by noting the expression is invariant under permutation of the two particles.…”
Section: Model For Asymmetric Entangled Double-slit Experimentsmentioning
confidence: 74%
“…Moreover, (27) allows application of this complementarity relation to any experiment where a CV is subjected to a binary-outcome measurement: one should have it evolve in a manner analogous to propagation of the double-slit wavefunction to the far-field; afterwards, an interference pattern should be extracted, either an actual one or some analogue; and finally, computation of the envelope-based visibility allow finding the "θ" and consequentially the predictability, thus inferring the strength of entanglement.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The outcome of a measurement carried out on a spin-1/2 particle can turn out to be 100 [1,2]. What is exactly measured in these procedures, and whether this carries physical meaning has been debated ever since the introduction of the concept of postselected values [3][4][5][6][7]. These anomalies emerge when an observable is measured through an indirect procedure, i.e.…”
mentioning
confidence: 99%
“…no operations/ losses). The weak values, 0 and 1, always satisfy such a definite relation with the probabilities [3], while it has been recently shown that the system with a weak value affects the other system as if it were in an eigenstate with eigenvalue equal to the weak value under the weak correlation [38]. In this sense the weak value of −1 has an important implication in relation to these definite weak values: −1 is the value which negates the definite value of 1 (probability 1) to be the definite value of 0 (probability 0).…”
mentioning
confidence: 99%